Hans Kelsen: A Peacemaker Through Law - Patrono, Mario (Victoria University of Wellington Law Review, 2014)
Mario Patrono has made many visits to New Zealand, and to Victoria University of Wellington School of Law in particular, during the course of his career. Most recently he has been a Visiting Professor at the Law School, arriving for the first trimester of 2013, 2014, and soon 2015, enjoying Wellington’s calmer autumn months, then sensibly returning to Rome before winter takes hold. During each of these visits Professor Patrono leads a seminar class on the fundamentals of European Union law for honours and masters students. He also contributes to the intellectual life of the Law School more generally, speaking at staff and student events. This article is based on one of those speaking engagements. The context of this talk was a Law School student seminar on the history and theory of international law led by Dr Guy Sinclair. Professor Patrono was invited to introduce the students to the work of Hans Kelsen. In this lecture he outlines Kelsen’s background and key works for this audience, touching on subjects such as Kelsen’s departure from Europe and early reception in the United States, before challenging those present with the notion that Kelsen’s work might have something to offer New Zealand constitutional scholarship.